Kesiapan Guru dalam mengimplementasikan Kurikulum merdeka belajar Pada Pembelajaran PAI di SDN 11 Kubu Tapan - Saaduddin Saaduddin (Departement of Mathematics Education, 2023)
The success of the learning process cannot be separated from the teacher's ability to develop learning models or strategies that are oriented towards increasing the intensity of student involvement effectively in the learning process. However, there are still teachers who have difficulty making lesson plans and require quite a long time allocation. And it is also difficult for teachers to prepare for authentic assessment in the aspects of attitudes, knowledge and skills using various assessment rubrics. This study used qualitative research methods. The key informants in this research were the school principal, teachers and students. Data collection techniques use observation, interviews and documentation. Data analysis consists of Data Reduction, Data Display and Verification and Drawing Conclusions. Research Results (1) Teacher readiness in preparing independent learning learning plans. It was found that teachers were not ready for an independent curriculum by preparing learning tools; (2) the teacher's physical condition is not ready, where it is difficult for the teacher to carry out all components of the independent curriculum; (3) mental and emotional conditions that teachers are not ready for, seen from the teacher's point of view, many of them are carried away by the implementation of the 2013 curriculum; (4) in terms of needs, it is in accordance with the needs of students; (5) teacher skills require mature readiness in their application.